Preparation method and application of spherical alumina carrier

The spherical alumina carrier was prepared by nuclear coating method, and the problems of low strength, uneven particle size, poor spherical and poor wear resistance in the prior art were solved, and the preparation of a carrier with high strength, uniform particle size and high spherical shape was achieved.

CN116571227BActive Publication Date: 2025-04-29ZHEJIANG TWRD NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310327861.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-30
Publication Date
2025-04-29
Estimated Expiration
2043-03-30

AI Technical Summary

Technical Problem

The alumina carrier prepared in the existing rotary molding technology has low strength, uneven particle size, poor spherical shape and poor wear resistance.

Method used

The spherical alumina carrier is prepared by the nuclear-making coating method, and the small-sized spherical core is formed through the combined use of a sugar-coated machine and the shot blasting machine. The particle size uniformity and spherical degree are improved through multiple screening and coating processes.

Benefits of technology

It improves the mechanical strength and sphericality of the alumina carrier, has uniform particle size and low wear rate, and is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116571227B_ABST
    Figure CN116571227B_ABST
Patent Text Reader

Abstract

The present invention provides a preparation method and application of a high-strength spherical alumina support. The preparation method includes uniformly mixing pseudoboehmite powder and a binder, denoted as powder A; preparing acid solution B and acid solution C; adding powder A to a sugar coating machine and spraying acid solution B for nucleation; screening the ball nuclei with a size of 0.6 - 1 mm after shot peening and shaping the ball nuclei, putting them into a shot peening machine, adding powder A and acid solution B in multiple times, screening out the ball nuclei with a size of 1.2 - 1.4 mm, adding them into the shot peening machine, adding powder A and acid solution C in multiple times, and the water-powder ratio of the powder A and acid solution C added each time is 0.85 - 1.11, so that the small balls grow to 2 - 2.2 mm; and successively undergoing drying and calcination to obtain the product. The obtained alumina support has a mechanical strength as high as 43 N, a wear rate of 0.1411%, uniform particle size, a specific surface area of 305 - 349 m<supgt;2 / < / supgt;g. After loading the active component, the active component is concentrated on the surface of the small balls. The spherical alumina support loaded with platinum tin is applied to the propane direct dehydrogenation reaction and shows performance comparable to that of the powder catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of industrial catalysis and relates to a preparation method and application of a spherical alumina carrier, and specifically relates to a method for preparing an alumina carrier with high strength, good sphericity, uniform particle size and large specific surface area by rotational molding, and the application of the alumina carrier in the dehydrogenation reaction of low-carbon alkanes. Background Art

[0002] In industrial applications, powder catalysts have problems such as high bed pressure drop, poor mass transfer and heat transfer, and cannot be directly applied to industrial reactions. Therefore, it is necessary to shape and process the basic research catalysts with development prospects into shaped catalysts with a certain shape, high mechanical strength and good pore structure. Liu Hongmei et al. found that the PDH catalytic performance of Pt catalysts is directly related to the physical structure of the carrier. The molding process will cause changes in the structural parameters of alumina, a decrease in specific surface area, a decrease in pore volume and a narrowing of the average pore size, which is not conducive to the dispersion of active components, and thus leads to a decrease in catalyst performance. Rosa et al.'s research shows that the performance of Pt catalysts in isobutane dehydrogenation reactions and catalytic reforming reactions is directly related to the pore structure characteristics of the alumina carrier. Therefore, molding research is also essential. How to prepare a carrier with high mechanical strength without reducing the permeability of the pores and maintaining the original reaction activity is the focus of current research.

[0003] According to statistics, the proportion of alumina used in all reactions is as high as 56.8%. Due to different catalytic reaction types, reaction processes and reactor types, alumina is usually prepared into certain shapes when used in industry, such as granular, spherical, circular, cylindrical, honeycomb, fibrous and special shapes (such as trilobal, porous cylindrical, toothed spherical and micro-spherical). Spherical catalysts have the advantages of uniform filling, uniform and stable fluid resistance, high bulk density, large loading and processing capacity, good wear resistance, high adsorption efficiency or reaction efficiency. Strip-shaped or other shaped carriers are mostly used in fixed bed reactors, while spherical carriers are more used in complex process devices such as moving beds or fluidized beds, which can make industrial reactions more efficient and improve production capacity and product yield. It has become a major trend in the domestic market to upgrade strip products to spherical products.

[0004] The main molding methods for spherical catalyst carriers include rotation molding, extrusion molding, spray drying molding, oil-ammonia column molding, oil column molding and water column molding.

[0005] Among them, the rotational molding method is to put the alumina precursor and an appropriate amount of binder into a rotating disc ball rolling machine, add water and peptizing agent during the rotation of the ball rolling machine, and the materials adhere to each other under the action of liquid bridges and capillaries, and gradually grow into spherical particles of a certain size. The advantages of the rotational molding method are low equipment investment and low cost, large processing volume and high production capacity; the disadvantages are low particle density, poor strength, uneven particle size, and dust pollution during operation. CN111389387A provides a rotational molding method for a residual oil hydrogenation spherical alumina carrier. The technical scheme first uses acid to treat the surface of pseudo-boehmite powder, and then dries it after static curing for a period of time. Atomized water is added to the disc molding machine to gradually shape it, and the moisture content of the material is controlled during the molding process. The final product is a low-wear carrier with a sphericity of more than 96%. Its bulk density and pore size distribution can be freely adjusted, but due to the use of acid curing, the specific surface area is low, only ~200m 2 / g.

[0006] Therefore, how to further improve the rotational molding process and prepare an alumina carrier with high mechanical strength and large specific surface area needs further research and development. Summary of the invention

[0007] The purpose of the present invention is to overcome the shortcomings of the alumina carrier prepared by the existing rotational molding technology, such as low strength, uneven particle size, poor sphericity and poor wear resistance, and to provide a preparation method and application of a high-strength spherical alumina carrier.

[0008] The present invention provides a method for preparing a spherical alumina carrier, the method comprising the following steps:

[0009] (1) Pseudo-boehmite powder and binder are mixed evenly and recorded as powder A; the concentration is

[0010] 3.00-4.00wt% and 3.90-5.56wt% dilute acid solutions are respectively recorded as acid solution B and acid solution C; powder A is added into a sugar coating machine, and during the rotation of the sugar coating machine, acid solution B is sprayed onto powder A to form cores to generate small particle size cores, and the cores are taken out when the particle size is less than 1mm;

[0011] (2) Shot blast the core and then screen it to get 0.6-1mm;

[0012] (3) Put the 0.6-1 mm ball core into the shot blasting machine, add powder A and acid solution B, repeat the above operation 14-16 times to make it agglomerate or coat and grow, and screen out the 1.2-1.4 mm ball core;

[0013] (4) Add 1.2-1.4 mm ball cores to the shot blasting machine, add powder A and acid solution C, repeat the above operation, the water-to-powder ratio of powder A and acid solution C added each time is 0.85-1.11, and gradually coat and shape the balls until they grow to 2-2.2 mm;

[0014] (5) The wet pellets are sequentially dried and calcined to obtain the product.

[0015] The selected acid is one or more of nitric acid, citric acid and acetic acid; preferably nitric acid.

[0016] In step (1), the water-to-powder ratio (mass ratio of water in the acid solution to pseudo-boehmite) of the powder A and the acid solution B added to the sugar coating machine is 0.96-0.97.

[0017] The water-to-powder ratio of the powder A and the acid solution B added each time in step (3) is 0.672-0.679.

[0018] The concentration of acid solution B is 3.00-3.60 wt %.

[0019] The mass of powder A added each time in step (4) is Where: ΔM is the mass of pseudo-boehmite added each time, unit: g; a is the mass of the ball in the shot blasting machine, unit: g; ρ is the density of the ball, unit: g / cm 3 ; r is the radius of the current ball, unit: cm; Δr is the increased thickness of the ball, unit: cm.

[0020] In steps (3) and (4), after each addition of powder A, rotate for 0.5-1.5 minutes, then add the acid solution and rotate for 3-5 minutes.

[0021] The binder in sample A is hydroxypropyl methylcellulose, and the mass ratio of hydroxypropyl methylcellulose to pseudo-boehmite is 0.02-0.05.

[0022] The speed of the sugar coating machine in the core making process is 36.8-46.0r / min, the speed of the shot blasting machine in the agglomeration (core growth) and coating process is 193-290r / min, and the wind speed is 1Hz.

[0023] The calcination temperature is 600-1200°C and the calcination time is 2-5h.

[0024] The invention also provides a supported catalyst, comprising the spherical alumina carrier, wherein active components are concentratedly distributed on the surface of the spheres.

[0025] The supported catalyst is a platinum-tin catalyst.

[0026] The present invention also provides an application of the platinum-tin catalyst in the dehydrogenation reaction of low-carbon alkanes.

[0027] The conditions for propane dehydrogenation are: H2 flow rate 3.4-3.6 mL / min, C3H8 flow rate 5.9-6.1 mL / min, reaction temperature 550-650°C, and reaction time 5-10 h.

[0028] The present invention prepares a spherical alumina carrier by a core-making coating method, thereby solving the problems of low strength, low sphericity, uneven particle size and poor wear resistance of alumina during rotational molding. During the core-making process, the sugar coating machine rotates to increase the contact area between the powder and the liquid adhesive, and the powder particles collide with each other. Under the action of capillary force and atmospheric pressure, the nuclei are aggregated into nuclei, and the formed spherical nuclei gradually grow into larger spherical nuclei through contact and collision processes in a shot blasting machine. Screening the spherical nuclei twice can solve the problem of uneven particle size. If the particle size does not meet the standard, it can be recycled to continue agglomeration or coating growth, thereby reducing the scrap rate and loss. After the spherical nuclei reach 1.2-1.4 mm, a powder of suitable quality is added. The small balls are subjected to the pressure of the wall and the collision between the small balls in the shot blasting machine, and grow evenly in the form of layered coating, with very little agglomeration, so as to prepare smooth small balls of uniform size. After drying and calcination, a high-strength spherical alumina carrier is obtained.

[0029] The beneficial effects of the present invention are as follows: the present invention uses pseudo-boehmite as raw material, and prepares a spherical alumina carrier through nucleation, screening and coating. The preparation process is simple, repeatable, easy to operate and scale up, and the mechanical strength of the alumina carrier is as high as 43N, which meets the requirements of industrial applications. The wear rate is 0.1411%, which can reduce the loss in transportation and is more suitable for industrial applications. In addition, the particle size of the spherical alumina carrier is 1.8-2mm, the sphericity is 99.3%, and the specific surface area is 305-349m 2 / g. The spherical alumina carrier carries active components, and the active components are concentrated on the surface of the spheres. The spherical alumina carrier carries platinum tin and is used in the direct dehydrogenation reaction of propane, showing performance comparable to that of powder catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a photo of the alumina pellets of Example 4.

[0031] Figure 2 This is a photo of the alumina pellets of Comparative Example 2.

[0032] Figure 3 This is a cross-sectional scanning electron microscope (SEM) image of the alumina support prepared in Example 4.

[0033] Figure 4 This is a scanning electron microscope (SEM) image of the cross section of the alumina support in Comparative Example 2.

[0034] Figure 5 Small pellets to prepare catalyst and changes after reaction.

[0035] Figure 6 The catalytic performance of Pt / Sn-Al2O3 in the PDH reaction was obtained using the spherical alumina and powdered alumina of Example 4 as carriers. DETAILED DESCRIPTION

[0036] In order to make the purpose and technical solution of the present invention clearer, the present invention is described in detail in combination with the following examples. The specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0037] Example 1

[0038] This example is used to illustrate the spherical alumina carrier prepared by the method of the present invention.

[0039] Pseudo-boehmite and 3wt% hydroxypropyl methylcellulose were stirred in a mixer for 2 minutes and mixed evenly to form mixed powder A. Dilute nitric acid solutions with concentrations of 3.60wt% and 5.38wt% were prepared as binder solutions, which were recorded as solutions B and C respectively. 500g of powder A was added to a sugar coating machine, and the speed of the sugar coating machine was adjusted to 36.8r / min. 500g of solution B was sprayed in, with an acid-powder ratio (mass ratio of acid to pseudo-boehmite) of 0.036 and a water-powder ratio of 0.964. The powder particles agglomerated into micro-nuclei under the action of capillary force and atmospheric pressure, and the spherical core was taken out when it was less than 1mm. The spherical core was added to a shot blasting machine for rounding, and then taken out for screening, and the 0.6-1.0mm core was collected for standby use. Take 200g of core, adjust the fan to 1Hz, adjust the speed of the shot blasting machine to 193r / min, add 15g of powder A, rotate for 1min, spray 10.5g of solution B, adjust the speed to 290r / min for 3min, repeat this process (adjust back to 193r / min, add 15g of powder A, rotate for 1min, spray 10.5g of solution B, adjust the speed to 290r / min for 3min) 15 times. Screen out the cores of 1.2-1.4mm (accounting for more than 80%), discard those larger than this particle size, and recycle those smaller than this particle size. Add 1.2-1.4mm cores into the shot blasting machine, with a fan frequency of 1Hz and a turntable speed of 193r / min. Add powder A to increase the radius by 8 microns and turn for 1min. Then add solution C with an acid-powder ratio of 0.05 and a water-powder ratio of 0.88 within 30s. Adjust the speed to 290r / min and turn for 3min. Repeat the addition of powder A and solution C. The mass of powder A added each time is Where: ΔM is the mass of pseudo-boehmite added each time, unit: g; a is the mass of the ball in the shot blasting machine, unit: g; ρ is the density of the ball, unit: g / cm 3; r is the radius of the current ball, unit: cm; Δr is the thickness of the ball, unit: cm. The ball is wrapped layer by layer and grows to 2.2 mm. The wet alumina ball after coating is dried at room temperature overnight, dried at 25 ° C for 6 hours, and dried at 50 ° C for 18 hours; the calcination temperature is increased at a rate of 1 ° C / min and continued at 600 ° C for 2 hours.

[0040] As a result, a spherical alumina carrier A was obtained. The physicochemical properties of the carrier were tested and shown in Table 1.

[0041] Example 2

[0042] This example is used to illustrate the spherical alumina carrier prepared by the method of the present invention.

[0043] Pseudo-boehmite and 3wt% hydroxypropyl methylcellulose were stirred in a mixer for 2 minutes and mixed evenly to form mixed powder A. Dilute nitric acid solutions with concentrations of 3.60wt% and 5.38wt% were prepared as binder solutions, which were recorded as solutions B and C respectively. 500g of powder A was added to the sugar coating machine, and the speed of the sugar coating machine was adjusted to 36.8r / min. 500g of solution B was sprayed in, with an acid-to-powder ratio of 0.036 and a water-to-powder ratio of 0.964. The powder particles agglomerated into micro-nuclei under the action of capillary force and atmospheric pressure, and the spherical core was taken out when it was less than 1mm. The spherical core was added to the shot blasting machine for rounding, and then taken out for screening, and the 0.6-1.0mm core was collected for standby use. Take 200g of core, adjust the fan to 1Hz, adjust the speed of the shot blasting machine to 193r / min, add 15g of powder A, rotate for 1min, spray 10.5g of solution B, adjust the speed to 290r / min for 3min, repeat this process (adjust back to 193r / min, add 15g of powder A, rotate for 1min, spray 10.5g of solution B, adjust the speed to 290r / min for 3min) 15 times. Screen out the cores of 1.2-1.4mm, discard those larger than this particle size, and recycle those smaller than this particle size. Add 1.2-1.4mm cores into the shot blasting machine, with a fan frequency of 1Hz and a turntable speed of 193r / min. Add powder A to increase the radius by 8 microns and turn for 1min. Then add solution C with an acid-powder ratio of 0.05 and a water-powder ratio of 0.88 within 30s. Adjust the speed to 290r / min and turn for 3min. Repeat the addition of powder A and solution C. The mass of powder A added each time is Where: ΔM is the mass of pseudo-boehmite added each time, unit: g; a is the mass of the ball in the shot blasting machine, unit: g; ρ is the density of the ball, unit: g / cm 3; r is the radius of the current ball, unit: cm; Δr is the thickness of the ball, unit: cm. The balls are wrapped layer by layer and grow to 2.2 mm. Take 200 g of the product after the growth is completed and continue to add 84.1 g of dilute nitric acid with a concentration of 5.38 wt% during the rotation process for curing. After the curing, the wet alumina balls are dried at room temperature overnight, dried at 25 ° C for 6 hours, and dried at 50 ° C for 18 hours; the calcination temperature is increased at a rate of 1 ° C / min at 600 ° C for 2 hours.

[0044] As a result, a spherical alumina carrier B was obtained. The physicochemical properties of the carrier were tested and are shown in Table 1.

[0045] Example 3

[0046] This example is used to illustrate the spherical alumina carrier prepared by the method of the present invention.

[0047] Pseudo-boehmite and 3wt% hydroxypropyl methylcellulose were stirred in a mixer for 2 minutes and mixed evenly to form mixed powder A. Dilute nitric acid solutions with concentrations of 3.60wt% and 5.38wt% were prepared as binder solutions, which were recorded as solutions B and C respectively. 500g of powder A was added to the sugar coating machine, and the speed of the sugar coating machine was adjusted to 36.8r / min. 500g of solution B was sprayed in, with an acid-to-powder ratio of 0.036 and a water-to-powder ratio of 0.964. The powder particles agglomerated into micro-nuclei under the action of capillary force and atmospheric pressure, and the spherical core was taken out when it was less than 1mm. The spherical core was added to the shot blasting machine for rounding, and then taken out for screening, and the 0.6-1.0mm core was collected for standby use. Take 200g of core, adjust the fan to 1Hz, adjust the speed of the shot blasting machine to 193r / min, add 15g of powder A, rotate for 1min, spray 10.5g of solution B, adjust the speed to 290r / min for 3min, repeat this process (adjust back to 193r / min, add 15g of powder A, rotate for 1min, spray 10.5g of solution B, adjust the speed to 290r / min for 3min) 15 times. Screen out the cores of 1.2-1.4mm, discard those larger than this particle size, and recycle those smaller than this particle size. Add 1.2-1.4mm cores into the shot blasting machine, with a fan frequency of 1Hz and a turntable speed of 193r / min. Add powder A to increase the radius by 8 microns and turn for 1min. Then add solution C with an acid-powder ratio of 0.05 and a water-powder ratio of 0.88 within 30s. Adjust the speed to 290r / min and turn for 3min. Repeat the addition of powder A and solution C. The mass of powder A added each time is Where: ΔM is the mass of pseudo-boehmite added each time, unit: g; a is the mass of the ball in the shot blasting machine, unit: g; ρ is the density of the ball, unit: g / cm 3; r is the radius of the current ball, unit: cm; Δr is the thickness of the ball, unit: cm. The ball grows layer by layer until the ball grows to 2.2 mm. Take 200g of the product after the growth is completed and add 100.17g of deionized water during the rotation process. The wet alumina ball after curing is dried at room temperature overnight, dried at 25℃ for 6h, and dried at 50℃ for 18h; the calcination temperature is increased at a rate of 1℃ / min at 600℃ for 2h.

[0048] As a result, a spherical alumina carrier C was obtained. The physicochemical properties of the carrier were tested and shown in Table 1.

[0049] Example 4

[0050] This example is used to illustrate the spherical alumina carrier prepared by the method of the present invention.

[0051] Pseudo-boehmite and 3wt% hydroxypropyl methylcellulose were stirred in a mixer for 2 minutes and mixed evenly to form mixed powder A. Dilute nitric acid solutions with concentrations of 3.60wt% and 5.26wt% were prepared as binder solutions, which were recorded as solutions B and C respectively. 500g of powder A was added to a sugar coating machine, and the speed of the sugar coating machine was adjusted to 36.8r / min. 500g of solution B was sprayed in, with an acid-to-powder ratio of 0.036 and a water-to-powder ratio of 0.964. The powder particles agglomerated into micro-nuclei under the action of capillary force and atmospheric pressure, and the spherical core was taken out when it was less than 1mm. The spherical core was added to a shot blasting machine for rounding, and then taken out for screening, and the 0.6-1.0mm core was collected for standby use. Take 200g of core, adjust the fan to 1Hz, adjust the speed of the shot blasting machine to 193r / min, add 15g of powder A, rotate for 1min, spray 10.5g of solution B, adjust the speed to 290r / min for 3min, repeat this process (adjust back to 193r / min, add 15g of powder A, rotate for 1min, spray 10.5g of solution B, adjust the speed to 290r / min for 3min) 15 times. Screen out the cores of 1.2-1.4mm, discard those larger than this particle size, and recycle those smaller than this particle size. Add 1.2-1.4mm cores into the shot blasting machine, with a fan frequency of 1Hz and a turntable speed of 193r / min. Add powder A to increase the radius by 8 microns and turn for 1min. Then add solution C with an acid-powder ratio of 0.05 and a water-powder ratio of 0.90 within 30s. Adjust the speed to 290r / min and turn for 3min. Repeat the addition of powder A and solution C. The mass of powder A added each time is Where: ΔM is the mass of pseudo-boehmite added each time, unit: g; a is the mass of the ball in the shot blasting machine, unit: g; ρ is the density of the ball, unit: g / cm 3; r is the radius of the current ball, unit: cm; Δr is the thickness of the ball, unit: cm. The ball is wrapped layer by layer and grows to 2.2 mm. The wet alumina ball after coating is dried at room temperature overnight, dried at 25 ° C for 6 hours, and dried at 50 ° C for 18 hours; the calcination temperature is increased at a rate of 1 ° C / min and continued at 600 ° C for 2 hours.

[0052] As a result, a spherical alumina carrier D was obtained. The physicochemical properties of the carrier were tested and are shown in Table 1.

[0053] Example 5

[0054] This example is used to illustrate the spherical alumina carrier prepared by the method of the present invention.

[0055] Pseudo-boehmite and 3wt% hydroxypropyl methylcellulose were stirred in a mixer for 2 minutes and mixed evenly to form mixed powder A. Dilute nitric acid solutions with concentrations of 3.60wt% and 5.26wt% were prepared as binder solutions, which were recorded as solutions B and C respectively. 500g of powder A was added to a sugar coating machine, and the speed of the sugar coating machine was adjusted to 36.8r / min. 500g of solution B was sprayed in, with an acid-to-powder ratio of 0.036 and a water-to-powder ratio of 0.964. The powder particles agglomerated into micro-nuclei under the action of capillary force and atmospheric pressure, and the spherical core was taken out when it was less than 1mm. The spherical core was added to a shot blasting machine for rounding, and then taken out for screening, and the 0.6-1.0mm core was collected for standby use. Take 200g of core, adjust the fan to 1Hz, adjust the speed of the shot blasting machine to 193r / min, add 15g of powder A, rotate for 1min, spray 10.5g of solution B, adjust the speed to 290r / min for 3min, repeat this process (adjust back to 193r / min, add 15g of powder A, rotate for 1min, spray 10.5g of solution B, adjust the speed to 290r / min for 3min) 15 times. Screen out the cores of 1.2-1.4mm, discard those larger than this particle size, and recycle those smaller than this particle size. Add 1.2-1.4mm cores into the shot blasting machine, with a fan frequency of 1Hz and a turntable speed of 193r / min. Add powder A to increase the radius by 8 microns and turn for 1min. Then add solution C with an acid-powder ratio of 0.05 and a water-powder ratio of 0.90 within 30s. Adjust the speed to 290r / min and turn for 5min. Repeat the addition of powder A and solution C. The mass of powder A added each time is Where: ΔM is the mass of pseudo-boehmite added each time, unit: g; a is the mass of the ball in the shot blasting machine, unit: g; ρ is the density of the ball, unit: g / cm 3; r is the radius of the current ball, unit: cm; Δr is the thickness of the ball, unit: cm. The ball is wrapped layer by layer and grows to 2.2 mm. The wet alumina ball after coating is dried at room temperature overnight, dried at 25 ° C for 6 hours, and dried at 50 ° C for 18 hours; the calcination temperature is increased at a rate of 1 ° C / min and continued at 600 ° C for 2 hours.

[0056] As a result, a spherical alumina carrier E was obtained. The physicochemical properties of the carrier were tested and are shown in Table 1.

[0057] Comparative Example 1 (not according to the present invention)

[0058] Pseudo-boehmite and 3wt% hydroxypropyl methylcellulose were stirred in a mixer for 2 minutes and mixed evenly to form mixed powder A. Dilute nitric acid solutions with concentrations of 3.60wt% and 5.88wt% were prepared as binder solutions, which were recorded as solutions B and C respectively. 500g of powder A was added to the sugar coating machine, and the speed of the sugar coating machine was adjusted to 36.8r / min. 500g of solution B was sprayed in, with an acid-to-powder ratio of 0.036 and a water-to-powder ratio of 0.964. The powder particles agglomerated into micro-nuclei under the action of capillary force and atmospheric pressure, and the spherical core was taken out when it was less than 1mm. The spherical core was added to the shot blasting machine for rounding, and then taken out for screening, and the 0.6-1.0mm core was collected for standby use. Take 200g of core, adjust the fan to 1Hz, adjust the speed of the shot blasting machine to 193r / min, add 15g of powder A, rotate for 1min, spray 10.5g of solution B, adjust the speed to 290r / min for 3min, repeat this process (adjust back to 193r / min, add 15g of powder A, rotate for 1min, spray 10.5g of solution B, adjust the speed to 290r / min for 3min) 15 times. Screen out the cores of 1.2-1.4mm, discard those larger than this particle size, and recycle those smaller than this particle size. Add 1.2-1.4mm cores into the shot blasting machine, with a fan frequency of 1Hz and a turntable speed of 193r / min. Add powder A to increase the radius by 8 microns and turn for 1min. Then add solution C with an acid-powder ratio of 0.05 and a water-powder ratio of 0.80 within 30s. Adjust the speed to 290r / min and turn for 3min. Repeat the addition of powder A and solution C. The mass of powder A added each time is Where: ΔM is the mass of pseudo-boehmite added each time, unit: g; a is the mass of the ball in the shot blasting machine, unit: g; ρ is the density of the ball, unit: g / cm 3 ; r is the radius of the current ball, unit: cm; Δr is the thickness of the ball, unit: cm. The ball is wrapped layer by layer and grows to 2.2 mm. The wet alumina ball after coating is dried at room temperature overnight, dried at 25 ° C for 6 hours, and dried at 50 ° C for 18 hours; the calcination temperature is increased at a rate of 1 ° C / min and continued at 600 ° C for 2 hours.

[0059] As a result, a spherical alumina carrier F was obtained. The physicochemical properties of the carrier were tested and shown in Table 1.

[0060] Comparative Example 2 (not according to the present invention)

[0061] Preparation of alumina spherical carrier by rotational molding

[0062] Weigh 500g of pseudo-boehmite and 15g of hydroxypropyl methylcellulose, stir for 2min using a mixer, and mix well. Weigh 36.76g of 68wt% concentrated nitric acid and dissolve it in 438.24g of deionized water to prepare a 5.26wt% dilute nitric acid solution, the acid-powder ratio of the ball-forming process is 0.045, and the water-powder ratio is 0.80. Add the mixed powder into the sugar coating machine, adjust the speed to 36.8r / min, spray nitric acid solution into the rising area of ​​the powder to mix the liquid and powder evenly, change the particle size, quality and adhesion, grow to ~2mm particles, and discharge; add the plastic particles into the shot blasting machine, adjust the fan frequency to 1Hz, and the turntable speed to 241.67r / min for shot blasting. The surface of the particles will become wet, and a very small amount of powder will be added before adhesion. After the sphericity is good, discharge; dry at room temperature overnight, dry at 25℃ for 6h, and dry at 50℃ for 18h; roast and heat at a rate of 1℃ / min at 600℃ for 2h.

[0063] As a result, a spherical alumina carrier G was obtained. The physicochemical properties of the carrier were tested and are shown in Table 1.

[0064] Table 1 Physicochemical properties of carrier AG

[0065] Strength / (N) Wear / (%) <![CDATA[Bulk density / (g / cm 3 )]]> Vector A 32.8 0.3019 0.785 Vector B 35.3 0.3425 0.852 Vector C 36.7 0.1827 0.788 Carrier D 37.3 0.3419 0.752 Carrier E 43.0 0.1411 0.813 Vector F 16.3 0.2129 0.759 Vector G 10.0 0.4794 0.618

[0066] As shown in the results of Examples 1-5, Comparative Examples 1-2 and Table 1, the strength of the spherical alumina carrier prepared by the method of the present invention is significantly increased. The water-powder ratio and shot blasting time are both influencing factors. The mechanical strength is low at an inappropriate water-powder ratio. The wear of this method is much lower than that of the conventional method, which is beneficial to reduce the shedding of active ingredients and the loss during transportation. Figure 1 As shown in FIG. 1 , the alumina spheres prepared by the present invention have a high sphericity of 99.3% and a uniform particle size of 2 mm. Figure 2 As shown, the particle size of the alumina spheres prepared in Comparative Example 2 is uneven, and the mass proportion of spheres with a diameter of 1.6-2 mm is only 22.19%. The specific gravity of the pseudo-boehmite after sintering is 364 m 2 / g, while the specific surface area of ​​carrier A, D and carrier G is 349m 2 / g, 306m 2 / g and 286m 2 / g, the specific surface area of ​​the carrier prepared by the present invention decreases less than that of the powder. Compared with the rotational molding method, the method of the present invention has high strength, high bulk density, uniform and easy-to-control spherical particle size, and high yield.

[0067] pass Figure 3 and Figure 4 By comparison, it can be seen that the broken cross-section of the alumina pellets prepared by the nucleation coating method is smooth and flat, with a few holes on the edge and a relatively rough center, which is a particle accumulation structure. The outer layer of the pellets is formed by the coating, which is tightly connected, has a layered structure, and the interlayer surface is smooth. The pellets have high compressive strength and can effectively withstand fluid pressure in a moving bed or fluidized bed reaction device, thereby increasing the service life of the catalyst. However, the pellets prepared by the rotational molding method have large holes inside, reaching tens of microns, which are gaps caused by the agglomeration of large particles. The holes will affect the strength, resulting in low compressive strength of the pellets.

[0068] 500 mg of the spherical alumina carrier prepared in Example 4 was immersed in water with a mass concentration of 9.377×10 -3 The catalyst was prepared by adding 0.3 wt% Pt and 0.6 wt% Sn to a 350 μL ethanol solution of 0.0128 mg / μL H2PtCl6·6H2O and 0.0128 mg / μL SnCl2·2H2O, standing for 2 h and then vacuum drying. The catalyst was then calcined at 500 °C in air for 4 h to obtain a platinum-tin catalyst. The loading amounts of platinum and tin were 0.3 wt% and 0.6 wt%, respectively. Figure 5 As shown in the figure, the cross section of the spherical catalyst is eggshell-shaped, and the active components are concentrated on the surface of the sphere. Under the conditions of H2 flow rate 3.6mL / min, C3H8 flow rate 6mL / min, reaction temperature 618℃, reaction time 6h, and powder catalyst were compared. Figure 6 It can be seen that at the beginning of the reaction, the spherical catalyst has a greater propane conversion rate, propylene selectivity and propylene yield. Overall, the carrier-supported catalyst prepared by the invention can show comparable performance to the powder catalyst.

[0069] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0070] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0071] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing a spherical alumina carrier, characterized in that: The following steps are involved: (1) Pseudo-boehmite powder and a binder are uniformly mixed, which is recorded as powder A; dilute acid solutions with concentrations of 3.00-4.00wt% and 3.90-5.56wt% are prepared, which are recorded as acid solution B and acid solution C, respectively; Powder A is added into a sugar coating machine. During the rotation of the sugar coating machine, acid solution B is sprayed onto powder A to form cores, thereby generating small-sized cores. The cores are taken out when the size is less than 1 mm. (2) Shot blast the core and then screen it to get 0.6-1 mm; (3) Put the 0.6-1 mm ball core into the shot blasting machine, add powder A and acid solution B, repeat the above operation 14-16 times to make it agglomerate or coat and grow, and screen out the 1.2-1.4 mm ball core; (4) Adding 1.2-1.4 mm ball cores into a shot blasting machine, adding powder A and acid solution C, repeating the above operation, wherein the water-to-powder ratio of powder A and acid solution C added each time is 0.85-1.11, and gradually coating and molding, so that the small balls grow to 2-2.2 mm, wherein the water-to-powder ratio is the mass ratio of water in the acid solution to pseudo-boehmite; (5) drying and calcining the wet pellets to obtain a spherical alumina carrier; In steps (3) and (4), after each addition of powder A, rotate for 0.5-1.5 min, then add the acid solution and rotate for 3-5 min.

2. The method for preparing a spherical alumina carrier according to claim 1, characterized in that: In step (1), the water-to-powder ratio of the powder A and the acid solution B added to the sugar coating machine is 0.96-0.97, and the water-to-powder ratio is the mass ratio of water in the acid solution to pseudo-boehmite.

3. The method for preparing a spherical alumina carrier according to claim 1, characterized in that: The water-to-powder ratio of the powder A and the acid solution B added each time in step (3) is 0.672-0.679, and the water-to-powder ratio is the mass ratio of water in the acid solution to pseudo-boehmite.

4. The method for preparing a spherical alumina carrier according to claim 1, characterized in that: The binder in sample A is hydroxypropyl methylcellulose, and the mass ratio of hydroxypropyl methylcellulose to pseudo-boehmite is 0.02-0.

05.

5. The method for preparing a spherical alumina carrier according to claim 1, characterized in that: The speed of the sugar coating machine during the core making process was 36.8-46.0 r / min, the speed of the shot blasting machine during the agglomeration and coating process was 193-290 r / min, and the wind speed was 1 Hz.

6. A supported catalyst, characterized in that: The invention comprises a spherical alumina carrier obtained by the method of claim 1, wherein the active components are concentratedly distributed on the surface of the spheres.

7. A supported catalyst as claimed in claim 6, characterized in that: The supported catalyst is a platinum-tin catalyst.

8. Use of the supported catalyst according to claim 7 in the dehydrogenation reaction of light alkanes.

Citation Information

Patent Citations

  • Rolling forming method of spherical alumina carrier of residual oil hydrogenation catalyst

    CN111389387A

  • Rolling molding method for spherical titanium-aluminum composite oxide

    CN103861660A

  • Preparation method of spherical alumina carrier

    CN104907103A